Polish students’ opinion about medicinal cannabis - Rafał Mazur; Sebastian Masternak; Michał Pająk; Katarzyna Parszewska; Katarzyna Skórzyńska-Dziduszko (Journal of Education, Health and Sport, 2017)
Introduction and the aim: According to statistics, in 2014 marijuana was used by 183 million of people, representing 2.5% of the world's population. However, marijuana also found its application in medicine. There is an evidence on the therapeutic benefits of cannabinoids in certain disease states. The aim of our study was to examine the attitude of the Polish students to medical marijuana and their knowledge on the use of cannabis in medicine. We were also interested in the opinion of students whether they accept the use of this therapy in Poland and which medical marijuana distribution channel they consider most appropriate.